PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, REPUTASI KAP LEVERAGE DAN UMUR PERUSAHAAN TERHADAP AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2012-2016 - Moch Norrochim Mashuri, 16.05.62.0006; Kartika, Andi (Students Journal of Accounting and Banking, 2018)
The purpose of this research is to analyze the influence of Profitability, Company Size, KAP Reputation, Leverage and Age of the Company to audit delay at manufacturing company listed in Indonesia Stock Exchange Period Year 2012-2016. The results of this analysis concluded that: Profitability and Company size negatively affects audit delay. KAPs reputation and Leverage do not affect audit delay and The companyâs Age positively affect audit delay.Keywords: Profitability, Company Size, KAP Reputation, Leverage, Age of the Company and audit delay